Evaluating the effectiveness of the integrated research subject research-based learning online (IRS-RBLO) model: retrospective record review study - Suwanbamrung, Charuai; Israel, Eskinder; Mehraj, Sandeep Kumar; Stanikzai, Muhammad Haroon; Ageru, Temesgen Anjulo; Jaroenpool, Jiraporn; Pibul, Panatda; Shohaimi, Shamarina; Kercho, Melkamu Worku (BioMed Central, 2025)
Background: The Integrated research subject-research-based learning online (IRS-RBLO) model is developed based on research-based learning, the components of the research process, and elements of online learning design. We aimed to evaluate the effectiveness of the IRS-RBLO in enhancing the learning outcome and research knowledge among community public health students at Walailak University, Thailand. Methods: This study applied a retrospective record review of 67 complete records out of 80 fourth-year community public health students of Walailak University to study the effectiveness of the IRS-RBLO model through research knowledge and learning outcomes. Research knowledge and learning outcomes were assessed using 40 multiple choice questions and 40 Likert scale questioners, respectively. The T-test was applied to analyze research knowledge before (1st week) and during learning (7th week), and ANOVA statistics to analyze students’ learning outcomes before (1st week), during (7th week), and after (16th week) learning with the IRS-RBLO model. Results: Students exhibited a significant difference in research knowledge (p =.00), with 35.88% percentage increase in aggregate knowledge assessment score before and during; and learning outcomes before, during, and after learning with the IRS-RBLO model (P =.00), with 17.44% increase in overall learning outcome increase between the scores of before and after. However, it showed variable results while comparing before and during (P <.001), before and after (P =.001), and during and after (P =.045) learning with the IRS-RBLO model. Conclusions: The IRS-RBLO model has shown its significant difference in research knowledge and learning outcomes. We recommend the broader implementation of the model, and future research may explore instructor opinions, and investigate educational policy implications to further validate the model’s effectiveness. Clinical trial number: Not applicable.